Hikayatnima / Muhammad Zahid Azzuhri Mustapha - Mustapha, Muhammad Zahid Azzuhri (College of Creative Arts, Universiti Teknologi MARA, Kedah, 2024)
In the world of event planning, "HikayatNima" stands out as a bright tribute to Malaysian history within the creative portfolio of "ACG Festiverse." While the ACG Festiverse thrives on Anime, Comic, and Gaming cultures, HikayatNima stands out as a cultural cosplay event that weaves together Malay, Chinese, Indian, and other Malaysian cultures. ACG Festiverse, founded in 2022 , plays an important role in commemorating Malaysia's Anime, Comic and Gaming scene. Frankie Ng Teck Seng, the creator behind these immersive experiences, inspired the creation of HikayatNima as a means of capturing cultural nuances. HikayatNima emerges from the complex tapestry of ACG Festiverse's event portfolio as a vibrant celebration of Malaysian cultural history, deviating from the Anime, Comic, and Gaming focus to highlight the rich amalgamation of Malay, Chinese, Indian, and other local customs. Despite the popularity of ACG Festiverse, the absence of Malay cultural aspects revealed a fundamental gap in expressing Malaysia's unique character. To address this, considerable efforts were made, including the creation of a dedicated website, collaborations with cultural custodians, custom marketing, a distinctive logo, and a fascinating video commercial..